Ultraviolet Radiation Index Over Ota, Nigeria - R. Usikalu, M.; V. Omotosho, T.; O. Ndubuisi, A.; A. Achuka, J.; J Abodunrin, T.; Bello, T. (International Journal of Engineering and Technology, 2018)
The sun has been observed to emit radiation in three major wavelengths; visible light (400-700nm), infrared radiation (700-1000nm) and ultraviolet radiation (UV) (3.0-400nm). UV possesses a short wavelength, hence, it is more energetic when compared to radiation of longer wavelengths. Davis wireless vantage pro2 weather station was used to obatin the UV radiation data over Ota, Ogun State, Nigeria from May 2012 to December 2013. The research revealed that mean UV index was 5.37. The UV peak time was consistently 12 noon for year 2012, while it was found to be 1:00 pm in March and April for 2013. Thus, the study observed that UV index over Ota is in the moderate range.Â Â